Kuala Lumpur urban biodiversity: birds community in urban public parks - Hj. Baharuddin, Zainul Mukrim; Rusli, Fatin Nadia; Othman, Rashidi (Pak Publishing Group, 2014)
Due to the growing number of human population, numerous developments are needed up until today. Thus, it has caused massive changes to the landscape; from natural to built environment. Consequently, the earth is confronting critical issues on protection and restoration of biodiversity. The impact of urbanization on biodiversity concerns on the relationship between biodiversity and urban ecosystem. The aim of this paper is to investigate abundance of urban biodiversity and its benefits to the urban communities. The triangulation methodology addresses a three-step-approach of biodiversity which are; observation, atmospheric measurement and human dimension. This study will present the abundance of bird observation in year 2010 and 2014. 11 species of birds were identified. The highest number of birds recorded is (Passer Montanus/Eurasian Tree-Sparrow (n=296) in 2010 and (n=116) in 2014. It is recorded that there are decreasing number of birds’ species such as Zebra Dove and Magpie Robin. There are new species identified in 2014; the Black Crowned Night Heron and Japanese sparrow hawk which are rarely found in urban area. The study presents an empirical survey on bird species. The declining area of green space in urban vicinity has affected the bird species population. It is suggested that bird conservations in urban context should be emphasized. It could improve the ecosystem services as well as health and well-being benefits of both wildlife and humans.